Livros independentes: os caminhos da autopublicação - PINHEIRO, Iranildo Junior de Souza (2019)
Sees independent publishing as an alternative for authors who do not reach the radar and interest of the traditional publishing market or want to have total autonomy during the creative process, with self-editing. It aims to approach the concept of self-publishing, the role of the librarian, and to relate librarianship to editorial production. Uses the bibliographical research based on the work of Martins, Chartier, Maimone and Thálamo, Lupton and Tschichold. It resort to the exploratory-descriptive method and the researcher's personal experience in the practice of editorial production. It develops a description of the production process of the book "O passer do meu viver", carried out by a student-editor. It concludes that the work of the librarian is easily inserted at any stage in the editorial context, since the formation allied with personal interest prepares him for editorial production.